BER estimation of optical WDM RZ-DPSK systems through the differential phase Q - Hiew, C. C.; Abbou, F. M.; Chuah, Hean Teik; Majumder, Satya Prasad; Abdul Rashid, Hairul Azhar (IEEE, 2004)
The optical return-to-zero differential phase-shift keying system is analyzed to determine the accuracy of the differential phase Q method in estimating the bit-error rate (BER). It is found that it consistently underestimates the BER though it successfully predicts the qualitative behavior of single-channel and wavelength-division-multiplexed systems for back-to-back and point-to-point configurations. A simple modification reduced the underestimation and produced accurate results.